Interrelation of competitive activity indicators, special, physical and functional fitness of highly qualified bmx cyclists - Semaeva, G. N.; Kvashuk, P, V.; Kostyukov, P. P.; Chernyshov, M. S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the relationship between the indicators of competitive activity, special physical and functional readiness of highly qualified BMX cyclists.